(untitled) (Bioresearch Communications, 2023)
Multidrug resistance (MDR) poses a global health threat, necessitating the exploration of alternative solutions. Probiotics, especially lactic acid bacteria (LAB), offer promising options against the impending crisis due to their recognized safety and potential health benefits. Probiotic potential characterization and selection of candidate LAB strains are highly crucial in probiotic product formulation. This study aimed to identify LAB from dairy product yogurt and evaluate their potential probiotic properties, i.e. aggregation capacity; tolerance to gastric and intestinal conditions; as well as antimicrobial potency. Ten LAB isolates were characterized based on colony characteristics, cellular morphology, and biochemical tests. The LAB isolates, both single and in mixed consortia, displayed a time-dependent increase in auto-aggregation, ranging from 21% to 71% after 5 hours of incubation. Isolate SW2 exhibited the highest auto-aggregative capability (65%). Co-aggregation studies revealed varying degrees of co-aggregation between probiotic LAB and pathogens, with some isolates showing stronger interactions (YD3, SW1, and SW2). Mixed consortia from sample TT demonstrated the highest co-aggregative ability with all tested pathogens. These findings highlight the potential of these isolates to form protective clusters, aiding in their survival and colonization within the gastrointestinal (GI) tract, besides the competitive exclusion of pathogens. The isolates demonstrated good tolerance to simulated gastric and intestinal conditions, as indicated by their non-significant reduction (only 1-2 log) in the bacterial count after 180 minutes of treatment. These findings indicate that LAB isolates can withstand harsh GI conditions, highlighting their suitability as probiotics. Antimicrobial profiles of the LAB isolates were evaluated using radial streak method and turbidimetric microtiter plate assay against eight MDR diarrheal and Uro-pathogens (n=4 for each). LAB isolates SKY1, SW1, SW3 and TT1 exhibited the highest antimicrobial activities; while pathogens DP2, UP41 and UP42 showed the most sensitivity. Exhibited antimicrobial activity of the LAB isolates points to their potential as formidable weapons against MDR infections. Overall, the results indicate that dairy-derived LAB isolates used in this study exhibit potential probiotic traits. Further research is warranted for their mechanisms, safety, efficacy, and use in probiotic supplement development. Bioresearch Commu. 9(2): 1340-1350, 2023 (July)